Penafsiran Ayat-Ayat tentang Perampasan Aset Koruptor dalam Perspektif Al-Misbah, Al-Azhar, Ibnu Katsir, dan Al-Munir - Ira Nazhifatul Qalbah; Wildan Taufiq; Badruzzaman M Yunus (CV. ALIM'SPUBLISHING, 2024)
This study discusses the interpretation of verses of the Qur'an related to the illegal taking of other people's property, especially in the context of the confiscation of corruptor assets, based on the views of Muhammad Quraish Shihab (Tafsir Al-Misbah), Hamka (Tafsir Al-Azhar), Ibn Kathir (Tafsir al-Qur'an al-'Azhim), and Wahbah Zuhaili (Tafsir al-Munir). This study uses a qualitative method with a library research approach to conceptually examine various things that are correlated with corruption from the perspective of the Qur'an. Therefore, this study is a type of qualitative and thematic research through literature review, namely by writing, reducing, and presenting data and analyzing it, as well as the theory of maqashid sharia and jinayah. The results of the study show that the commentators support the confiscation of corruptors' assets as a legitimate action in Islam, by the principles of maqashid al-syariah, especially the protection of property (hifz al-mal). Quraish Shihab emphasizes the importance of asset confiscation to restore justice and protect society. Hamka sees this action as a just punishment that also restores the rights of society. Ibn Kathir emphasizes that corruption must be punished strictly to prevent greater damage. Wahbah Zuhaili emphasizes the authority of the government in upholding justice and preventing injustice, including through the confiscation of illegal assets. This interpretation provides a strong theological basis for the policy of asset confiscation as part of the enforcement of Islamic law, emphasizing that such action is necessary to maintain balance and stability in society.